Cognitive Risks of Professional Skepticism in Auditing - Redko О. Yu. (Statistics of Ukraine, 2025)
The article elaborates on an uncommon but disregarded theme. It touches upon issues of implementing the principle of profession skepticism in the auditing practice and related cognitive risks. Professional skepticism is a key principle of auditing, requiring critical thinking and doubt concerning the sufficiency and reliability of the proofs. But the adherence to it quite often entails cognitive risks affecting the auditor’s ability to resist an external pressure and preserve impartiality. The author gives a detailed analysis of the following risks: experience effect, aberration of freshness, effects of shared opinion and self-assuredness, absolutization of results, confirmation bias, excessive trust in client-side controls, etc. The author systematized the main reasons for the occurrence of cognitive risks in auditing: the necessity of effective actions given limited time and human resources; ambiguity, inadequate scopes or material inconsistencies in the obtained information; too large scopes of information requiring scrutiny and analysis in quite a short time span. Such risks may undermine the objectivity of auditor’s judgments, affect the quality of auditor’s opinions and create potential gaps in identifying material misstatements. The awareness and elimination of these risks requires non-stop learning, introduction of structured procedures, and fostering ethical culture in auditing firms. The author believes that professional skepticism is an option that ensures public demand for auditor’s services and lays the fundament for high performance of the auditor’s effort. The author is convinced that professional skepticism needs to be addressed with emphasis on the semantical perspective. This principle is realized through a system chain of auditor’s thinking: doubt (or lack of confidence) – distrust – scrupulousness – caution – prudence. This is the way of implementing professional skepticism in the auditing practice. Disagreeing with the thesis that suspicion is a trait intrinsic in auditors, the author suggests that professional skepticism is the fundament for auditing practices in combination with another principle of audit, professional independence. The author comes to the conclusion that avoiding cognitive risks is a tall order for an auditor. At the same time, regulatory acts on audit require quality assurance in auditing along with the adherence to the principle of professional skepticism through a series of preventive measures.